Evaluation of gilteritinib in combination with chemotherapy in preclinical models of FLT3-ITD(+) acute myeloid leukemia - Ueno, Yoko (Oncotarget, 2019)
Activating internal tandem duplication (ITD) and tyrosine kinase domain (TKD) point mutations in Fms-like tyrosine kinase 3 (FLT3) occur in approximately 30% of patients with acute myeloid leukemia (AML), and confer a poor prognosis with standard cytarabine/anthracycline or azacitidine-based chemotherapy regimens. Gilteritinib is a highly-specific, potent FLT3/AXL inhibitor with demonstrated activity against FLT3-ITD and FLT3-TKD mutations. Compared with salvage chemotherapy, treatment with once-daily oral gilteritinib demonstrated a clinical benefit in patients with FLT3-mutated relapsed/refractory AML, which led to its recent approval in Japan and the United States. We investigated the effects of gilteritinib combined with cytarabine plus daunorubicin/idarubicin, or combined with azacitidine in human FLT3-ITD–positive (FLT3-ITD(+)) AML cell lines and xenografted mouse models. Gilteritinib induced G(1) arrest and apoptosis in a dose-dependent manner. The addition of cytarabine, daunorubicin, idarubicin, or azacitidine potentiated apoptosis. Gilteritinib alone or combined with cytarabine, daunorubicin, idarubicin, or azacitidine, inhibited anti-apoptotic protein expression in MV4-11 cells. In xenografted mice, administration of cytarabine, idarubicin, or azacitidine in combination with gilteritinib had little impact on plasma or intratumor PK profiles of gilteritinib, cytarabine, idarubicin, or azacitidine. Gilteritinib combined with chemotherapy reduced tumor volume to a greater extent than either gilteritinib or chemotherapy alone. Of note, the addition of cytarabine plus daunorubicin/idarubicin led to tumor regression in mice, with complete regression observed in six out of eight mice in both triple combination groups. These findings support the investigation of gilteritinib combined with chemotherapy in patients with FLT3-ITD(+) AML, including those who are ineligible for intensive chemotherapy.